2021
DOI: 10.1016/j.mtbio.2021.100100
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive glasses and glass–ceramics for hyperthermia treatment of cancer: state-of-art, challenges, and future perspectives

Abstract: Bioactive glasses and glass-ceramics are well-proven potential biomaterials for bone-tissue engineering applications because of their compositional flexibility. Many research groups have been focused to explore the utility of bioactive glass–ceramics beyond bone engineering to hyperthermia treatment of cancer. Hyperthermia refers to raising the temperature of tumor close to 44°C at which malignant cells perish with negligible harm to normal cells. Hyperthermia can be employed by many means such as by ultrasoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 188 publications
0
29
0
Order By: Relevance
“…More importantly, BGs show a unique feature for regenerative medicine, i.e., their capability of bonding to human tissues, known as “bioactivity.” Over time, specific formulations of biocompatible glasses were developed to further expand and tune their biological properties for specific conditions in the body, such as cancer treatment [10] , [11] , [12] . In this regard, a series of metallic and non-metallic elements can be added to the basic composition of BGs to render anticancer activities [13] , [14] , [15] . For instance, iron (Fe) was successfully incorporated in glasses for rendering osteostimulatory multi-functions, such as improved bone metabolism through enhanced calcification, osteoblast proliferation, as well as apatite-forming ability [16] , [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, BGs show a unique feature for regenerative medicine, i.e., their capability of bonding to human tissues, known as “bioactivity.” Over time, specific formulations of biocompatible glasses were developed to further expand and tune their biological properties for specific conditions in the body, such as cancer treatment [10] , [11] , [12] . In this regard, a series of metallic and non-metallic elements can be added to the basic composition of BGs to render anticancer activities [13] , [14] , [15] . For instance, iron (Fe) was successfully incorporated in glasses for rendering osteostimulatory multi-functions, such as improved bone metabolism through enhanced calcification, osteoblast proliferation, as well as apatite-forming ability [16] , [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
“…The slower reaction rate of CDT based on Fenton reaction is also a major factor limitation of the effectiveness of CDT ( Cao et al, 2021 ). The high temperature from hyperthermia therapy (HT) can improve the rate of the Fenton/Fenton-like reaction to greatly increase the efficacy of CDT ( Liu et al, 2019 ; Danewalia and Singh, 2021 ). Recently, Shen et al (2020) reported MnFe 2 O 4 NPs functionalized with Ir (III) complexes (Ir@MnFe 2 O 4 NPs) for magnetic hyperthermia therapy (MHT) enhanced CDT.…”
Section: Ht Enhanced M-cdt Nanodrugsmentioning
confidence: 99%
“…In recent years, photothermal therapy (PTT), as a specific emerging cancer therapy, has been extensively researched in the field of tumor treatment (Liu et al, 2019;Danewalia and Singh, 2021). Many transition metal nanomaterials have been researched for PTT, such as MoS 2 -based nanomaterials (Jianling , CoS 2 nanomaterials (Wang et al, 2020a), copper-based nanomaterials (Ai et al, 2021;Wang et al, 2021b;Li et al, 2021), titanium-based nanomaterials (Wang et al, 2020b;Wang et al, 2021c), covalent organic frameworks (COFs) (Yao et al, 2021b), etc.…”
Section: Photothermal-enhanced Radiotherapymentioning
confidence: 99%